Creación de un sitio web turístico y recorrido virtual de los lugares turísticos del cantón Yantzaza. - Vélez Ludeña, Wilson Augusto (2012)
This thesis consists of CREATING A WEB SITE AND TOURISM VIRTUAL TOUR OF CANTON YANTZAZA TOURIST SITES. This research aims to show the importance of web technology in the development of tourism in the county in which Yantzaza define all aspects of technology related to the application of technology with high availability requirements and speed, defining all the methodological and technical to be considered for projects of tourist sites, which start from planning to execution, based on the systematic study directed and organized to enable end the problem under investigation. Next, make a complete design of the structure of the county's tourism website Yantzaza and tourist sites, taking into account their functional elements taking into account the most representative elements, subsystems, indicating the steps to follow for implementation. It should be noted that in addition to performing a module online room reservations for lodging in this county, and a virtual tour of some interesting sites of this canton. This application contains the most important of tourism in this district as the most important places, festivals, hotels, restaurants, local foods and online reservations module. Note that this application is properly documented manuals and user programmer for a better understanding, both in form and design. In the Methodology section has described the methods, materials and working techniques used throughout this research work. In the section on Methodology for the development of research, a brief description of the activities could be implemented by applying inductive and deductive methods. For its part the Development Methodology Tool highlights each of the phases that make up the Agile Software Development RUP. In the item on theoretical foundations, traces the history, definitions and specifications and graphs most important UML 2.0 provides for the preparation of diagrams. It also presents the definitions, characteristics and specifications of most relevance to e-tourism, online tourism advantages and benefits. And everything related to software development phases and for other important specifications. For his part, section Alternative Proposal Development, explains the steps taken for the construction of tourist website Yantzaza. In the first instance describes the problem identified in order to define the scope of the application. Below are the prototype screens, the use case description and diagrams in which we strengthened our position to document the software. Then leads to the definition of the development platform and programming policies. It also describes the activities carried out in stages Verification and Validation of the system to display the results subsequently achieved. Approach also makes some conclusions drawn as a result of the entire development process, and some recommendations for tourism website users and for administrators of it. Finally we develop a tourism website of the Canton Yantzaza and tourist sites, using the tools necessary to build this application as well as Object Oriented technologies.